2012
DOI: 10.4254/wjh.v4.i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic porto-systemic shunt in the elderly: Palliation for complications of portal hypertension

Abstract: AIM: To present a dedicated series of transjugular intrahepatic porto-systemic shunts (TIPS) in the elderly since data is sparse on this population group. METHODS: A retrospective review was performed of patients at least 65 years of age who underwent TIPS at our institutions between 1997 and 2010. Twenty-five patients were referred for TIPS. We deemed that 2 patients were not considered appropriate candidates due to their markedly advanced liver disease. Of the 23 patients suitable for TIPS, the indications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Meta‐analyses comparing TIPS with LVP reported TIPS to be more effective in reducing ascites recurrence, however with a greater incidence of HE (prevalence 15%‐61%); with conflicting survival outcome data . In one small retrospective study (n = 10) of palliative TIPS for RA ± hepatic hydrothorax in ESLD, 50% developed HE with more than half subsequently dying within three months …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta‐analyses comparing TIPS with LVP reported TIPS to be more effective in reducing ascites recurrence, however with a greater incidence of HE (prevalence 15%‐61%); with conflicting survival outcome data . In one small retrospective study (n = 10) of palliative TIPS for RA ± hepatic hydrothorax in ESLD, 50% developed HE with more than half subsequently dying within three months …”
Section: Discussionmentioning
confidence: 99%
“…4 In one small retrospective study (n = 10) of palliative TIPS for RA ± hepatic hydrothorax in ESLD, 50% developed HE with more than half subsequently dying within three months. 41 The ALFApump ® involves an implantable device pumping ascites from the peritoneal cavity into the bladder. 42 Consistent with the initial European multicentre safety and efficacy study and the multicentre RCT, 43,44 recent studies have corroborated complication rates of infections (11%-56%), 45,46 renal dysfunction (21%-67%), [45][46][47] device deficiency including catheter occlusion (9%-33%) 45,46 and explantation rates of up to 30%.…”
Section: What This Study Addsmentioning
confidence: 99%
“…TIPS results in lower re-bleeding rates and improved survival in patients who undergo TIPS for recurrent esophageal variceal bleeding or within 72 h of esophageal variceal bleeding [7,10,11]. The benefit for TIPS and refractory ascites is improvement in quality of life with decreased need for large volume paracentesis, while a survival benefit for this indication has not been consistently demonstrated [15,18,[22][23][24][25][26]. A well-recognized complication of TIPS is HE, which can be disabling and more disabling than the indication for TIPS, such as ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Prior retrospective studies have evaluated TIPS outcomes in patients 60 years and older [14][15][16] reporting increased rates of encephalopathy or short-term mortality in this older age group [12,14,[17][18][19][20][21]. The purpose of our study was to report outcomes after TIPS in patients 70 years of age and older including rates of HE and 30 d readmissions after TIPS.…”
Section: Introductionmentioning
confidence: 99%
“…Transjugular intrahepatic portosystemic stent shunt (TIPS) is an effective treatment for esophageal variceal hemorrhage caused by portal hypertension (1,2). It has been demonstrated that compared with medical treatment and endoscopic treatment, the early use of a TIPS in patients with hemorrhages improves the survival rate significantly.…”
Section: Introductionmentioning
confidence: 99%